The longitudinal association between children’s growth mindset in senior primary school and their parents’ growth mindset - Chen, Jiao; Liu, Chunhui (Frontiers in Psychology, 2023)
Growth mindset plays a positive role in children's development, but few studies use longitudinal data to investigate the development trajectory of children's growth mindset. In addition, previous studies have shown that there may be no intergenerational transmission of mindset, but the influence of parents' growth mindset on the development and change of children's growth mindset cannot be denied. Based on the abovementioned factors, the present study used a sample of fourth-grade primary school students and their parents in Beijing (N=4004), and five waves of longitudinal data over two and a half years were collected to identify the trajectories of growth mindset in senior primary school with latent growth modeling and to examine the effects of parents’ growth mindset with a parallel process latent growth model. The results showed the following. (1) The growth mindset of the senior primary school children decreased over time, and there were significant individual differences in the initial level and growth of mindset. (2) Children in senior primary school showed higher levels of growth mindset after two-and-a-half years if their mothers reported higher levels of growth mindset in the beginning. Children showed higher levels of growth mindset after two and a half years if their mothers’ growth mindset declined slower during this period, while they showed lower levels if their mothers’ growth mindset declined rapidly; the mothers’ growth mindset declines and the children's growth mindset would also show a downward trend during this time. Finally, (3) there was no significant relationship between both the initial level and the decline of the father's growth mindset and the development pattern of the children's growth mindset.